Historical, Philosophical and Ethical Roots of Artificial Intelligence - Şenocak, Dilek; Kocdar, Serpil; Bozkurt, Aras (PJE, 2023)
Artificial intelligence (AI) generally refers to the science of creating machines that carry out tasks inspired by human intelligence, such as speech-image recognition, learning, analyzing, decision making, problem solving, and planning. It has a profound impact on how we evaluate the world, technology, morality, and ethics and how we perceive a human being including its psychology, physiology, and behaviors. Hence, AI is an interdisciplinary field that requires the expertise of various fields such as neuroscientists, computer scientists, philosophers, jurists and so forth. In this sense, instead of delving into deep technical explanations and terms, in this paper we aimed to take a glance at how AI has been defined and how it has evolved from Greek myths into a cutting-edge technology that affects various aspects of our lives, from healthcare to education or manufacturing to transportation. We also discussed how AI interacts with philosophy by providing examples and counter examples to some theories or arguments focusing on the question of whether AI systems are capable of truly human-like intelligence or even surpassing human intelligence. In the last part of the article, we emphasized the critical importance of identifying potential ethical concerns posed by AI implementations and the reasons why they should be taken cautiously into account.